Revisiting Metal Sulfide Semiconductors: A Solution-Based General Protocol for Thin Film Formation, Hall Effect Measurement, and Application Prospects - Shinde, Dipak V.; Patil, Supriya A.; Cho, Keumnam; Ahn, Do Young; Shrestha, Nabeen K.; Mane, Rajaram S.; Lee, Joong Kee; Han, Sung-Hwan (WILEY-V C H VERLAG GMBH, 2015)
Nanostructured thin films of metal sulfides (MS) are highly desirable materials for various optoelectronic device applications. However, a general low-temperature protocol that describes deposition of varieties of MS structures, especially in their film form is still not available in literatures. Here, a simple and highly effective general solution-based deposition protocol for highly crystalline and well-defined nanostructured MS thin films from ethanol on variety of conducting and non-conducting substrates is presented. The films display remarkable electronic properties such as high carrier mobility and high conductivity. When NiS thin film deposited on a flexible polyethylene terephthalate (PET) substrate is used as a fluorine doped tin oxide (FTO)-free counter electrode in dye-sensitized solar cells, it exhibits a solar-to-electric power conversion efficiency of 9.27 +/- 0.26% with the highest conversion efficiency as high as 9.50% (vs 8.97 +/- 0.07% exhibited by Pt-electrode). In addition, the NiS film deposited on a Ti-foil has demonstrated an outstanding catalytic activity for the hydrogen and oxygen evolution reactions from water.
Keywords: SENSITIZED SOLAR-CELLS; CHEMICAL BATH DEPOSITION; FREE COUNTER ELECTRODE; ATOMIC LAYER DEPOSITION; REDUCED GRAPHENE OXIDE; ACTIVE EDGE SITES; HIGH-PERFORMANCE; VAPOR-DEPOSITION; NANOROD ARRAYS; CDS